2022
DOI: 10.1158/1078-0432.ccr-22-0433
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA–Based MRD Assessment in Patients with CLL Treated with Obinutuzumab, Acalabrutinib, and Venetoclax

Abstract: Purpose: With the advent of highly efficacious time-limited combination treatments of targeted agents in chronic lymphocytic leukemia (CLL), minimal residual disease (MRD) assessment has gained importance as a measure for therapeutic success and as a surrogate for progression-free survival. The currently most widely used method is multicolor flow cytometry, which detects circulating CLL cells in the peripheral blood. However, it seems to be less sensitive for the detection of MRD in the lymph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Taqman assays were designed using the Integrated DNA Technologies (IDT) primerquest tool (https://www.idtdna.com) deliberately spanning one or more V(D)J segment boundaries (determined by the IMGT tool) to increase specificity. Digital PCR assays were performed in triplicates using 4 μL containing a maximum amount of 80 ng cell‐free DNA per reaction as previously described 19 . Of note, each assay was tested with a set of negative controls containing no template, DNA obtained from peripheral blood mononuclear cells (pBMC) of a healthy donor, DNA obtained from a CLL sample, and DNA obtained from another rrDLBCL sample of the present study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taqman assays were designed using the Integrated DNA Technologies (IDT) primerquest tool (https://www.idtdna.com) deliberately spanning one or more V(D)J segment boundaries (determined by the IMGT tool) to increase specificity. Digital PCR assays were performed in triplicates using 4 μL containing a maximum amount of 80 ng cell‐free DNA per reaction as previously described 19 . Of note, each assay was tested with a set of negative controls containing no template, DNA obtained from peripheral blood mononuclear cells (pBMC) of a healthy donor, DNA obtained from a CLL sample, and DNA obtained from another rrDLBCL sample of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Digital PCR assays were performed in triplicates using 4 μL containing a maximum amount of 80 ng cell-free DNA per reaction as previously described. 19 Of note, each assay was tested with a set of negative controls containing no template, DNA obtained from peripheral blood mononuclear cells (pBMC) of a healthy donor, DNA obtained from a CLL sample, and DNA obtained from another rrDLBCL sample of the present study. In line with our previous study in chronic lymphocytic leukemia 19 and guidelines for the application of ddPCR in lymphoproliferative disorders, 22 samples were considered positive only when a fluorescence signal in the FAM channel was similar to the FAM signal in the positive control, a minimum number of three DNA fragments were supporting the variant (the dominant V(D)J-clone or the MYD88 p.L265P mutation), and the negative controls confirmed no signal.…”
Section: Digital Droplet Pcr and Assessment Of Minimal Residual Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have confirmed that CR or PR of the bone marrow is not very relevant in the presence of uMRD, and the outcome is not entirely clear in patients with inconsistent MRD results in PB and BM. To address these issues, attempts are being made to use cell-free DNA from plasma to measure MRD to provide information about residual disease in different compartments [ 65 , 66 ]. This assay also allows tracking and responding to the emergence of new clones and potential mutations.…”
Section: Using Mrd To Guide Time-limited Treatmentmentioning
confidence: 99%
“…Assessing the cell-free DNA (cfDNA) in plasma for CLL-associated VDJ rearrangements is a newer method that has the advantage of being able to analyze for residual disease across multiple compartments and, in theory, could assess the total body MRD after therapy with a sensitivity that appears at least similar, if not greater, than that of flow cytometry. 6 However, some of the limitations noted for detecting clonal VDJ rearrangements in DNA extracted from leukocytes also apply to assays for MRD in cfDNA; moreover, for unexplained reasons, detection of MRD in some patients (eg, those with del(11q)) appeared more readily achieved using flow cytometry than through analysis of cfDNA for idiosyncratic clonal VDJ rearrangements; this did not appear to be the case for patients lacking del(11q), suggesting that the sensitivity of this approach for monitoring MRD may be influenced by factors associated with the leukemia cell's cytogenetics.…”
mentioning
confidence: 99%